Managing Africa's natural resources : capacities for development - Hanson, Kobena T.; D'Alessandro, Cristina; Owusu, Francis; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
The authors investigate well-known concerns in natural resource management in Africa while focusing on the capacity dimension of the problems. They examine dynamics of leadership, governance, criminality, structural transformation, as well as emerging issues such as green growth.
Keywords: Science